Rapid screening and identification of antioxidants in the leaves of Malus hupehensis using off‐line two‐dimensional HPLC–UV–MS/MS coupled with a 1, 1′‐diphenyl‐2‐picrylhydrazyl assay. Issue 12 (21st May 2018) - Liu, Minzhuo; Huang, Xueqian; Liu, Qi; Chen, Miao; Liao, Sen; Zhu, Fawei; Shi, Shuyun; Yang, Hua; Chen, Xiaoqing
Abstract: The leaves of Malus hupehensis have a strong antioxidant activity and are commonly consumed as a healthy tea. However, detailed information about its antioxidants is incomplete. Herein, we developed an effective strategy based on combining off‐line two‐dimensional high‐performance liquid chromatography with ultraviolet and tandem mass spectrometry detection with a 1, 1′‐diphenyl‐2‐picrylhydrazyl assay to rapidly screen and identify the antioxidants from the leaves of M. hupehensis . In the orthogonal two‐dimensional liquid chromatography system, a Venusil HILIC column was used for the first dimension, while a Universil XB‐C18 column was installed in the second dimension. As a result, 32 antioxidants, including ten dihydrochalcones, two flavanones, nine flavonols, four flavones, and seven phenolic acids were tentatively identified, out of which 23 compounds, as far as we know, were isolated and characterized from the leaves of M. hupehensis for the first time. To the best of our knowledge, this is the first systematic investigation of the antioxidants from the leaves of M. hupehensis . The results indicated that the proposed method is an efficient technique to rapidly investigate antioxidants, especially for coeluted and minor compounds in a complex system.